Return to face-to-face learning in Costa Rican public schools: Student and Teacher opinions (Innovaciones Educativas, 2023)
In Costa Rica's formal education system, the teaching and learning process has always been face-to-face; however, in the face of the health emergency caused by COVID-19, in the years of highest incidence, 2020 and 2021, measures were taken to safeguard the health of the participants; therefore, in order to guarantee the educational process of the student body, distance and blended learning educational modalities were implemented. In this context, it was considered important to develop the research project to analyze the opinions of the teaching staff and students in six Costa Rican public schools in relation to the return to face-to-face attendance in 2022, after the implementation of the distance and combined educational process for two years. Eleventh grade students participated, in which they lived the experience in all modalities: face-to-face, distance, combined and again face-to-face. Teachers of different subjects who gave lessons to the same students also participated. In both cases it was expected to have opinions in relation to methodological processes, evaluation, relations with peers, attitudes towards the educational process and comparative visions in the return to full face-to-face attendance. The study was conducted under a quantitative approach and a questionnaire was used to collect information; the analysis was performed statistically by means of SPSS®. The most important conclusion is the vision found by students and teachers in the aspects valued, where students tend to have a more positive view of their teachers and that evaluation is one of the most important points in common between both populations.
Keywords: Pandemic; secondary education; academic teaching staff; presence at school; post pandemia; students; opinions